2018
DOI: 10.1007/s00405-018-4895-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-enhanced MRI in combination with color Doppler flow imaging for improving diagnostic accuracy of parotid gland lesions

Abstract: Combining CDFI with non-enhanced MRI can improve the diagnostic accuracy of MRI for classifying parotid gland lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Our previous studies confirmed the utility of apparent diffusion coefficient (ADC) in combination with color Doppler flow imaging [ 8 ] and multi-phasic computer tomography (CT) [ 9 ] for classifying parotid gland lesions into benign and malignant tumors. However, the results were still not entirely satisfactory.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our previous studies confirmed the utility of apparent diffusion coefficient (ADC) in combination with color Doppler flow imaging [ 8 ] and multi-phasic computer tomography (CT) [ 9 ] for classifying parotid gland lesions into benign and malignant tumors. However, the results were still not entirely satisfactory.…”
Section: Introductionsupporting
confidence: 66%
“…The diagnostic value of DWI in the characterization of parotid gland lesions is well recognized. Previous studies [ 8 , 23 ] pointed out that there were significant differences in ADC values among pleomorphic adenoma, Warthin’s tumor, and malignant tumor, while Warthin’s tumor had the lowest ADC values among these three. Paradoxically, Matsushima et al [ 24 ] found considerable limitations and no statistical difference in differentiation of benign from malignant parotid lesions by ADC values, possibly because Warthin’s tumor has a low ADC value due its mucus composition.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al [7] found that mean ADC value of 1.29 × 10 −3 mm 2 /s had 100% sensitivity and 91.7% specificity in differentiating pleomorphic adenoma from malignant parotid gland tumor. Several previous studies [7,[10][11][12][14][15][16][17][18] found that there was no significant difference between the mean ADC value of Warthin's tumor (mean ADC value ranged from 0.74 to 0.99 × 10 −3 mm 2 /s) and malignant parotid gland tumors (mean ADC value ranged from 0.795 to 1.21 × 10 −3 mm 2 /s). This is in agreement with our study.…”
Section: R E T R a C T E D A R T I C L Ementioning
confidence: 89%
“…Tao et al [12] found that mean ADC value of pleomorphic [14] stated that mean ADC values of pleomorphic adenoma and malignant parotid gland tumors was 1.35 × 10 −3 mm 2 /s and 0.94 × 10 −3 mm 2 /s respectively. Zang et al [15] found that mean ADC value of pleomorphic adenoma and malignant parotid gland tumors was 1.57 × 10 −3 mm 2 /s and 1.16 × 10 −3 mm 2 /s respectively. This is in agreement with our results where the mean ADC value for pleomorphic adenoma was 1.38 × 10 −3 mm 2 /s versus 1.08 × 10 −3 mm 2 /s for malignant parotid gland tumors (P = 0.046).…”
Section: R E T R a C T E D A R T I C L Ementioning
confidence: 99%
“…Therefore, differentiating between malignant and benign tumors based on B-mode and Doppler US is difficult and can lead to misdiagnosis. Zhang et al (2018) have showed that the diagnostic accuracy (96.1 vs 82.4%) of DWI-MRI was increased when ADC values were used in conjunction with US Doppler flow imaging features to differentiate parotid tumors compared to single usage of ADC values [24].…”
Section: Grayscale and Doppler Criteriamentioning
confidence: 99%